2009
DOI: 10.1007/s10519-009-9280-1
|View full text |Cite
|
Sign up to set email alerts
|

Feather Pecking in Domestic Fowl is Genetically Related to Locomotor Activity Levels: Implications for a Hyperactivity Disorder Model of Feather Pecking

Abstract: Feather pecking is a major welfare problem in egg production. Genetic lines differing in the level of feather pecking have been developed by genetic selection. In two experiments correlated responses in locomotor activity were investigated. Firstly, general locomotor activity was estimated using electronic transponders. A total of 325 pullets from three lines: an unselected control line (CON), a line selected for low levels of feather pecking (LFP) and a line selected for high levels of feather pecking (HFP) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 32 publications
6
71
2
Order By: Relevance
“…Therefore, we speculate whether the activity level is somewhat higher in the flocks with high levels of feather Table 4 Spearman's rank correlations between the variables at flock level (n = 30) collected at 62 weeks of age, that is, different floor feather characteristics, prevalence of droppings with feather content, density of floor feathers and prevalence of poor plumage condition scored by trained observers pecking causing the plucked feathers to be covered by litter more quickly or to accumulate in specific areas of the hen house, which is especially likely to occur with the light downy feathers. The studies by Kjaer (2009) and Kjaer et al (2015) support these speculations. They found that lines selected for high levels of feather pecking have a higher general activity level than low feather pecking lines and control lines with the latter being intermediate.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, we speculate whether the activity level is somewhat higher in the flocks with high levels of feather Table 4 Spearman's rank correlations between the variables at flock level (n = 30) collected at 62 weeks of age, that is, different floor feather characteristics, prevalence of droppings with feather content, density of floor feathers and prevalence of poor plumage condition scored by trained observers pecking causing the plucked feathers to be covered by litter more quickly or to accumulate in specific areas of the hen house, which is especially likely to occur with the light downy feathers. The studies by Kjaer (2009) and Kjaer et al (2015) support these speculations. They found that lines selected for high levels of feather pecking have a higher general activity level than low feather pecking lines and control lines with the latter being intermediate.…”
Section: Discussionmentioning
confidence: 60%
“…The occurrence of EFP birds may also be the result of the co-occurrence of SFP with other facilitating behaviors. Chickens from an HFP line were found to have significantly higher locomotor activity compared with chickens from an LFP (Kjaer, 2009;Lutz et al, 2016). Other behaviors, such as those involved in aggression (Bessei et al, 2013;Bennewitz et al, 2014), exploration (de Haas et al, 2010Brunberg et al, 2011) and fear Boegelein et al, 2014, Grams et al, 2015b have been reported to be associated with feather pecking and may have a complementary effect on this behavior.…”
Section: Discussionmentioning
confidence: 98%
“…There is evidence of line differences in FP (Kjaer et al 2001;Uitdehaag et al 2008), and it has been demonstrated that FP is influenced by group size, light intensity, diet and type of litter (Hughes and Duncan 1972;Blokhuis and Arkes 1984;Savory 1995). As for its aetiology, FP has been considered to be redirected ground pecking (Blokhuis 1986), abnormal dustbathing behaviour (Vestergaard and Lisborg 1993), or the consequence of a more general hyperactivity disorder (Kjaer 2009). Most of the evidence point at the redirected ground pecking theory (Huber-Eicher and Wechsler 1997), with active or even hyperactive birds having the highest risk of developing FP (Newberry et al 2007;Kjaer 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As for its aetiology, FP has been considered to be redirected ground pecking (Blokhuis 1986), abnormal dustbathing behaviour (Vestergaard and Lisborg 1993), or the consequence of a more general hyperactivity disorder (Kjaer 2009). Most of the evidence point at the redirected ground pecking theory (Huber-Eicher and Wechsler 1997), with active or even hyperactive birds having the highest risk of developing FP (Newberry et al 2007;Kjaer 2009). The serotonergic system has been shown to play an important role in the modulation of FP (van Hierden et al 2002(van Hierden et al , 2004a Edited by Stephen Clark Maxson.…”
Section: Introductionmentioning
confidence: 99%